Information security investment model: resource representation and organizational training - Milov, Oleksandr; Kostyak, Maryna; Milevskyi, Stanislav; Rzaev, Hazail Nuraddin Ogly (Національний технічний університет "Харківський політехнічний інститут", 2019)
Information technology (IT) protection is a key economic concern for organizations. While research in the field of investment in IT security is growing rapidly, they lack the theoretical basis for combining economic and technological phenomena and research directions. The proposed theoretical model is based on the use of the theory of organizational behavior and resource representation. The combined application of these theories allows, within the framework of one model, to present the organizational effects of training that arise when developing the protection of organizational resources using countermeasures of IT security. Identified approaches to the study of investments in information security, which boil down to the following: microeconomic approaches based on game theory, financial analysis based on return on investment (ROI), net present value (NPV) and internal rate of return (IRR), and management approaches based on decision theory, risk management and organization theory. The combination of various theories and approaches leads to the formation of a multi-theoretical model, which allows you to combine the methods of these research areas within the framework of a comprehensive model based on the resource representation and the theory of organizational learning. The difficulties of developing a theoretical model for investment in information security are indicated, namely: the diversity of the nature of countermeasures, covering strategic and operational issues, taking into account legal, technical andorganizational aspects; the intended purpose of investments in information security (risk reduction, not profit); the complementarity of the prospects for the operational and strategic periods. Various points of view on investment problems are presented, namely, resource representation and representation in the framework of the theory of organizational learning. The proposed approach allowed us to build an integrated model of investment in information security. Answers to questions arising from the analysis of the integrated model of investment in information security can not only determine future research, but also have managerial consequences that will help firms make informed investment decisions in the field of information security.

Захист інформаційних технологій (ІТ) є ключовою економічною проблемою для організацій. У той час як дослідження в області інвестицій в ІТ-безпеку швидко ростуть, у них відсутні теоретичні основи для об'єднання економічних і технологічних явищ і напрямків досліджень. Пропонована теоретична модель заснована на використанні теорії організаційної поведінки і ресурсного уявлення. Спільне застосування цих теорій дозволяє в рамках однієї моделі представити організаційні ефекти навчання, що виникають при розробці захисту організаційних ресурсівза допомогою контрзаходів ІТ-безпеки. Визначено підходи до вивчення інвестицій в інформаційну безпеку, які зводяться до наступних: мікроекономічні підходи, засновані на теорії ігор, фінансовий аналіз, заснований на прибутковості інвестицій (ROI), чистої приведеної вартості (NPV) і внутрішньої норми прибутку (IRR), і управлінські підходи, засновані на теорії прийняття рішень, управління ризиками та теорії організації. Об'єднання різних теорій і підходів призводить до формування мультитеоретичної моделі, яка дозволяє об'єднати методи зазначених напрямків досліджень врамках комплексної моделі, засновану на ресурсному поданні та теорії організаційного навчання. Вказані складності розробки теоретичної моделі для інвестицій в інформаційну безпеку, а саме: різноманітність природи контрзаходів, що охоплюють стратегічні та операційні питання з урахуванням правових, технічних і організаційних аспектів; цільове призначення інвестицій в інформаційну безпеку (зниження ризику, а не отримання прибутку); взаємодоповнюваність перспектив оперативного і стратегічного періодів. Представлені різні точки зору на проблеми інвестицій, а саме ресурсне уявлення і уявлення в рамках теорії організаційного навчання. Пропонований підхід дозволив побудувати інтегральну модель інвестицій в інформаційну безпеку. Відповіді на питання, що випливають з аналізу інтегральної моделі інвестицій в інформаційну безпеку можуть не тільки визначати майбутні дослідження, а й мати управлінські наслідки, які допоможуть фірмам приймати обґрунтовані інвестиційні рішення в області інформаційної безпеки.
Модель інвестицій в інформаційну безпеку: ресурсне подання та організаційне навчання
Keywords: resource representation; organizational theory of learning; integral investment model; ресурсне уявлення; організаційна теорія навчання; інтегральна модель інвестицій